Disease activity and two-year sacroiliac joint changes according to instrumental study findings in a CoRSAr cohort of patients with early axial spondyloarthritis - Sh. Erdes; D. G. Rumyantseva; A. V. Smirnov; T. V. Dubinina (Научно-практическая ревматология)
The evolution of axial spondyloarthritis (axSpA) and the transition of its nonradiographic to radiographic stage, when ankylosing spondylitis (AS) can be diagnosed, concern many researchers. To clarify this issue, an active search for predictors of the progression of this disease is underway; special cohort studies are being conducted.Objective: to analyze two-year changes in the magnetic resonance imaging (MRI) signs of sacroiliac joint (SIJ) inflammation and disease activity in patients with axSpA who form a Moscow CoRSAr cohort (a Cohort of early SpondylArthritis) and the role of these indicators in the progression of sacroiliitis.Subjects and methods. The investigation enrolled 68 CoRSAr cohort patients followed up for two years. All the patients underwent pelvic radiography and SIJ MRI at inclusion in the cohort and then every year. At inclusion in the cohort, nonradiographic axSpA was present in 28 patients, and AS was in 40. Disease activity was determined by BASDAI and ASDAS-CRP. The progression of sacroiliitis was assessed by the total scores of radiographic sacroiliitis.Results and discussion. The patients' age at inclusion in the cohort averaged 28.5±5.8 years, with a mean disease duration of 24.1±15.4 months and a male proportion of 51.5%; the HLA-B27-positive patients were 92.6%. At two years, 39% of the patients with nonradiographic axSpA went to the AS group. 24-month sacroiliitis progression was observed in 40% of the patients. Disease activity had little impact on the progression of sacroiliitis.Conclusion. Over two years, almost 40% of patients with axSpA showed an increase in the radiographic stage of sacroiliitis in the CoRSar cohort; this progression was primarily associated with the foci of osteitis according to MRI and correlated little with the activity of the disease.